PENGEMBANGAN MODUL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MEDIA FLIPBOOK DI SMAN 112 JAKARTA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - KHOIRUNISA, TUTIK; Sodiq, Akhmad; Maswani, Maswani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research generally aims to obtain a learning module for Islamic Religious Education based on flipbook media at SMAN 112 Jakarta. While specifically to analyze the implementation of learning with flipbook-based modules and analyze the effectiveness of flipbook-based modules. This research is a type of research and development (R&D). The research data source consisted of qualitative research in the form of in-depth interviews with Islamic Religious Education educators and students at SMAN 112 Jakarta. Meanwhile, quantitative data was obtained from the results of questionnaires (questionnaires) from experts, educators, and students who were analyzed using a Likert scale and t-test. The research findings show that the flipbook-based Islamic Religious Education learning module is feasible to use and effectively improves the learning outcomes of class X students of SMAN 112 Jakarta and can be used easily. The implications of the results of this study theoretically contribute to learning media developers and students because the modules are arranged based on the needs and characteristics of students. While the practical implications show that after participating in learning with flipbook-based modules the learning outcomes of students improve significantly, the average learning outcomes are above the Minimum Completeness Criteria (KKM).